GURU BIMBINGAN DAN KONSELING DI SEKOLAH DASAR SANGAT DIBUTUHKAN - Sukadari Sukadari (Universitas PGRI Yogyakarta, 2021)
The problem our pupils must face grow in complexity along with the development of age, especially at elementary level. At present many elementary grades require the availability of guidance and counseling. Elementary schools acting as classroom teacher while also providing guidance and counseling in practice is not viable. As such dedicated guidance counselor is needed to provide professional service. With the presence of guidance counselor, the quality of education can be developed further with the availability of optimum service for students tailored according to their needs and situation. Here the government is expected to hire guidance and counselor at elementary schools by following pattern at junior and senior high schools in which the counselor: student ratio is 1:150.